Menciptakan Dunia yang Lebih Adil melalui Pendidikan - Siti Rohmah Nurhayati (Fakultas Ilmu Pendidikan UNY, 2008)
The civilization growth of mankind has shown the existence of inequality between woman and men status. This is caused by difference of treatment between women and men since they were born. Many efforts conducted to solve the problem of gender inequality. One of the way to solve the problem is developing gender fair education. The goal of gender fair education is to reach equity and equality of gender at performance of national education development. It consists equity and equality of gender in aspects of